Therapeutic Potential of Solanum Alkaloids with Special Emphasis on Cancer: A Comprehensive Review - Manoharan R; Nair CS; Eissa N; Cheng H; Ge P; Ren M; Jaleel A (Dove Medical Press, 2024)
Ramya Manoharan,1 Chythra Somanathan Nair,1 Nermin Eissa,2 Hao Cheng,3 Pengliang Ge,4 Maozhi Ren,3 Abdul Jaleel1 1Department of Integrative Agriculture, College of Agriculture and Veterinary Medicine, United Arab Emirates University, Al Ain, United Arab Emirates; 2Department of Biomedical Sciences, College of Health Sciences, Abu Dhabi University, Abu Dhabi, United Arab Emirates; 3Institute of Urban Agriculture, Chinese Academy of Agricultural Sciences, Chengdu National Agricultural Science and Technology Center, Chengdu, People's Republic of China; 4College of Plant Science & Technology, Huazhong Agricultural University, Wuhan, People's Republic of ChinaCorrespondence: Abdul Jaleel, Department of Integrative Agriculture, College of Agriculture and Veterinary Medicine, United Arab Emirates University, Al Ain, United Arab Emirates, Tel +9713-7134558, Email abdul.jaleel@uaeu.ac.aeAbstract: Cancer has emerged as a formidable global health challenge, with treatment methods like chemotherapy and radiation often exacerbating the situation due to their associated side effects. Opting for natural sources like plants as a safer and environmentally friendly alternative seems promising. Historically, plants have served as valuable sources for treating diverse health conditions, attributable to their rich composition of therapeutic phytochemicals. Within this array of phytochemicals, alkaloids, especially those found in the Solanaceae plant family, are notably prominent. Alkaloids from Solanaceae plant family called Solanum alkaloids demonstrate noteworthy anti-tumour characteristics and exert a potent inhibitory influence on cancer cell proliferation. They trigger programmed cell death in cancerous cells through various molecular pathways, whether administered alone or combined with other medications. Solanum alkaloids act upon cancer cells via multiple mechanisms, including apoptosis induction, suppression of cell growth and migration, as well as inhibition of angiogenesis. This review provides insights into the anti-cancer attributes of Solanum alkaloids found in various Solanum plant species, along with a brief overview of their other medicinal properties.Keywords: Solanum alkaloids, anticancer, apoptosis, molecular mechanism, structure function relationship, therapeutic values